The new 'coN' staging system combining lymph node metastasis and tumour deposit provides a more accurate prognosis for TNM stage III colon cancer. (1st August 2022) - Wang, Xitao; Cheng, Wei; Dou, Xiaolin; Tan, Fengbo; Yan, Shipeng; Zhou, Zhongyi; Li, Yuqiang; Xu, Biaoxiang; Liu, Chongshun; Ge, Heming; Tian, Mengxiang; Liu, Fangchun; et al.
Abstract: Objective: Despite controversy over its origin and definition, the significance of tumour deposit (TD) has been underestimated in the tumour node metastasis (TNM) staging system for colon cancer, especially in stage III patients. We aimed to further confirm the prognostic value of TD in stage III colon cancer and to establish a more accurate 'coN' staging system combining TD and lymph node metastasis (LNM). Methods: Information on stage III colon cancer patients with a definite TD status was retrospectively collected from the Surveillance, Epidemiology and End Results (SEER) database between 2010 and 2017. The effect of TD on prognosis was estimated using Cox regression analysis. Maximally selected rank statistics were used to select the optimal cut‐off value of TD counts. The predictive power of conventional N staging and the new coN staging was evaluated and compared by Akaike's information criterion (AIC), Harrell's concordance index (C‐index) and time‐dependent receiver operating characteristic (ROC) curves. Clinicopathological data of stage III colon cancer patients in the Xiangya database from 2014 to 2018 were collected to validate the coN staging system. Results: A total of 39, 185 patients with stage III colon cancer were included in our study: 38, 446 in the SEER cohort and 739 in the Xiangya cohort. The incidence of TD in stage III colon cancer was approximately 30% (26% in SEER and 30% in the Xiangya database). TD was significantly associated with poorer overall survival (OS) (HR = 1.37, 95% CI 1.31–1.44, p < 0.001 in SEER). The optimal cut‐off value of TD counts was 4, and the patients were classified into the TD0 (count = 0), TD1 (count = 1–3) and TD2 (count ≥ 4) groups accordingly. The estimated 5‐year OS was significantly different among the three groups (69.4%, 95% CI 68.8%–70.0% in TD0; 60.5%, 95% CI 58.9%–62.2% in TD1 and 42.6%, 95% CI 39.2%–46.4% in TD2, respectively, p < 0.001). The coN system integrating LNM and TD was established, and patients with stage III colon cancer were reclassified into five subgroups (coN1a, coN1b, coN2a, coN2b and coN2c). Compared with conventional N staging, the coN staging Cox model had a smaller AIC (197097.581 vs. 197358.006) and a larger C‐index (0.611 vs. 0.601). The AUCs of coN staging at 3, 5 and 7 years were also greater than those of conventional N staging (0.6305, 0.6326, 0.6314 vs. 0.6186, 0.6197, 0.6160). Concomitant with the SEER cohort results, the coN staging Cox model of the Xiangya cohort also had a smaller AIC (2883.856 vs. 2906.741) and a larger C‐index (0.669 vs. 0.633). Greater AUCs at 3, 5 and 7 years for coN staging were also observed in the Xiangya cohort (0.6983, 0.6774, 0.6502 vs. 0.6512, 0.6368, 0.6199). Conclusions: Not only the presence but also the number of TDs is associated with poor prognosis in stage III colon cancer. A combined N staging system integrating LNM and TD provides more accurate prognostic prediction than the latest AJCC N staging in stage III colon cancer. Abstract : The coN staging combining TDs and LNMs results in more powerful prognositic prediction than the conventional N staging in stage III colon cancer.